ReCARving the future: bridging CAR T-cell therapy gaps with synthetic biology, engineering, and economic insights - Ali, Alaa; DiPersio, John F. (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of hematologic malignancies, offering remarkable remission rates in otherwise refractory conditions. However, its expansion into broader oncological applications faces significant hurdles, including limited efficacy in solid tumors, safety concerns related to toxicity, and logistical challenges in manufacturing and scalability. This review critically examines the latest advancements aimed at overcoming these obstacles, highlighting innovations in CAR T-cell engineering, novel antigen targeting strategies, and improvements in delivery and persistence within the tumor microenvironment. We also discuss the development of allogeneic CAR T cells as off-the-shelf therapies, strategies to mitigate adverse effects, and the integration of CAR T cells with other therapeutic modalities. This comprehensive analysis underscores the synergistic potential of these strategies to enhance the safety, efficacy, and accessibility of CAR T-cell therapies, providing a forward-looking perspective on their evolutionary trajectory in cancer treatment.